The nurse's role in risk classification through the Manchester Protocol in urgency and emergency services (Research, Society and Development, 2022)
The Manchester Protocol (MP) is an indispensable tool directed mainly to the management of emergency services in Brazil and in other countries, where patients are classified in triage by color scales, using signs and symptoms as a basis, thus observing the degree of complication, and waiting time until care. This study aimed to conduct an active search in the literature on the role of nurses in risk classification using the Manchester Protocol in urgency and emergency services. This is a descriptive study, using the Integrative Literature Review (ILR) technique, together with the PICO strategy for formulating the guiding question. The search was conducted between March and May 2021 in the indexed databases of the Virtual Health Library (VHL): LILACS, BDENF and MEDLINE by joining four Health Descriptors (DeCS) crossed with the Boolean operator "AND": Emergency Nursing AND Emergency Medical Services AND Nursing AND Triage. 479 articles were found in total. When adding the criteria of articles published in the last five years (2016 to 2021) within the Portuguese and English languages, this number reduced to 89. After reading and analyzing the research, 11 articles were selected to compose this study. The risk classification has numerous benefits for its users, with greater emphasis on reducing risks and preventable deaths, prioritization of care after evaluation of clinical criteria, extinction of triage by unqualified operation. Given the exposed information, it was verified the importance of the nursing professional facing the risk classification through the Manchester protocol in urgency and emergency units, being the professional directed and trained to perform the customer assessment.